The Characteristics of the Persona of Correctional Facility Employees, Who Unlawfully Applied Forceful Methods of Influence to Persons Deprived of Their Liberty - A. M. Smirnov (Сибирское юридическое обозрение, 2020)
The article outlines the signs characterizing the employees of correctional institutions who unlawfully applied forceful methods of influence to persons deprived of their liberty. These are mainly mature men who have experience working in correctional facilities, the necessary professional skills, an adequate level of education, whose personal life is prosperous. At the same time, they are characterized by so-called professional deformation and burnout, and in some cases – violation of labor discipline, unprofessional behavior. In addition, they are characterized by such negative personality traits as inability to self-control (self-control), emotional instability, lack of authority among prisoners, low stress tolerance, self-doubt, inability to reasonably act in difficult (extreme) situations. Knowledge of these negative personality traits of employees who unlawfully applied forceful methods to persons deprived of their liberty can be useful for developing effective measures to prevent the phenomenon under consideration in domestic prison practice.